Organizational Factors and Technology Innovation Acceptance Which Affects Success of Audit Information Systems for Certified Public Accountant - Sukwatanasinit, Kanoksak (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
The purpose of this research was (1) to study organizational factors affecting the success of the utilization of information systems in audit work in terms of quality of the system, quality of information, benefits, timeliness, and satisfaction of certified public accountants, and (2) to study the acceptance of technology innovation affecting the success of the utilization of information systems in audit work in terms of quality of the system, quality of information, benefits, timeliness, and satisfaction of certified public accountants. This was quantitative research using the questionnaire as a research tool. The population and sample were certified public accountants (CPAs). Data analysis and hypothesis testing to answer the research objectives. Descriptive statistical analysis was used, and inference statistical analysis was used by multiple regression analysis. The results of the research revealed that (1) the organizational factor in terms of the support of supervisors and the organizational structure had a positive influence on the success of using information systems in audit work. quality of the system, quality of information, benefits, timeliness, and satisfaction, in terms of personnel, there was a negative influence on the success of using information systems in audit work, system quality, benefits, and timeliness, and (2) the technology innovation acceptance factor in terms of performance expectations from use in terms of facilities, ease of use, and the expectation of trying to use had a positive influence on the success of using information systems in auditing. quality of the system, quality of information, benefits, timeliness, and satisfaction of certified public accountants.